Neural correlates of proactive and reactive aggression in adolescent twins. Issue 3 (21st October 2016) - Yang, Yaling; Joshi, Shantanu H.; Jahanshad, Neda; Thompson, Paul M.; Baker, Laura A.
Abstract : Verbal and physical aggression begin early in life and steadily decline thereafter in normal development. As a result, elevated aggressive behavior in adolescence may signal atypical development and greater vulnerability for negative mental and health outcomes. Converging evidence suggests that brain disturbances in regions involved in impulse control, emotional regulation, and sensation seeking may contribute to heightened aggression. However, little is known regarding the neural mechanisms underlying subtypes of aggression (i.e., proactive and reactive aggression) and whether they differ between males and females. Using a sample of 106 14‐year‐old adolescent twins, this study found that striatal enlargement was associated with both proactive and reactive aggression. We also found that volumetric alterations in several frontal regions including smaller middle frontal and larger orbitofrontal cortex were correlated with higher levels of aggression in adolescent twins. In addition, cortical thickness analysis showed that thickness alterations in many overlapping regions including middle frontal, superior frontal, and anterior cingulate cortex and temporal regions were associated with aggression in adolescent twins. Results support the involvement of fronto‐limbic‐striatal circuit in the etiology of aggression during adolescence. Aggr. Behav. 43:230–240, 2017. © 2016 Wiley Periodicals, Inc.